2022
DOI: 10.1001/jamanetworkopen.2022.26701
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Electric Scooter and Bicycle Injuries After Introduction of Electric Scooter Rentals in Oslo, Norway

Abstract: IMPORTANCEWhen society introduces and accepts new transportation modes, it is important to map risks and benefits. OBJECTIVE To compare electric scooter (e-scooter) and bicycle injuries. DESIGN, SETTING, AND PARTICIPANTS This cohort study is based on prospectively collected data on Norwegian patients who sustained e-scooter or bicycle injuries and presented to an emergency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…Stray et al reported that most patients with trauma from the use of stand-up electric scooters were young (in their 20s and 40s) and that the average age of such patients was lower than that of patients with bicycle-related trauma. 11 This is consistent with the fact that the average age of patients with trauma due to the use of stand-up electric scooters was lower than that of patients with bicycle-related trauma in this study. In addition, a comprehensive analysis of teeth injured due to the use of stand-up electric scooters and bicycles in this study revealed that 92.3% of the injured teeth were localized to anterior teeth.…”
Section: Re Sultssupporting
confidence: 91%
“…Stray et al reported that most patients with trauma from the use of stand-up electric scooters were young (in their 20s and 40s) and that the average age of such patients was lower than that of patients with bicycle-related trauma. 11 This is consistent with the fact that the average age of patients with trauma due to the use of stand-up electric scooters was lower than that of patients with bicycle-related trauma in this study. In addition, a comprehensive analysis of teeth injured due to the use of stand-up electric scooters and bicycles in this study revealed that 92.3% of the injured teeth were localized to anterior teeth.…”
Section: Re Sultssupporting
confidence: 91%
“…The differences could at least partly be explained by the fact that their number was an estimate and ours were based on exact figures. Interstingly, a recent study from Norway have presented a threefold incidence of accidents among scooters compared to bikes 16 . This can also be compared with accident rates for ED visits for bicycles from a prospective cohort study from Belgium 22 ; 3 per 100,000 trips, 5 per 1,000,000 km and 8 per 100,000 h. Therefore, it seems that electric scooter drivers travel a shorter distance and a shorter time before an accident occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Electric scooters for public rent were recently made illegal in the city of Copenhagen, Denmark 15 . Interestingly, the incidence of accidents for electric scooters is not well described and few comparison 16 has been made to other modes of transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Electric scooters (e-scooters) are associated with a high risk of injuries, especially injuries occurring at nighttime or under the influence of substances. 1 Several nighttime restrictions have been attempted to decrease the number of injuries, but the outcomes of those restrictions have been evaluated only without the use of user data. 2,3 In addition, only limited data have been reported about the user database incidences of e-scooter-related injuries.…”
Section: Introductionmentioning
confidence: 99%